Diversity of capitalism in the European post-socialist economies: The Balkan states at a crossroads - Mádr, Michal; Kouba, Luděk (Univerzita Pardubice, 2016)
The main aim of the paper is to classify the types of capitalism in the Balkan states in the context of the European post-socialist countries and identify the principal strengths and weaknesses of institutional organization in these countries. The paper uses Amable’s approach, which is supplemented by the influence of the political environment. The paper identifies two different capitalist clusters in the Balkan area: market economies (Bulgaria, Croatia, Montenegro and Romania) and hybrid economies (Albania, Bosnia and Herzegovina, Macedonia and Serbia). The Balkan countries are compared with the other post-socialist economies, the EU-8 and post-soviet countries. Within the Balkan States, only Croatia and Montenegro are approaching the EU-8 economies, while on the other hand, Albania has some characteristic in common with the Caucasian republics. In general, the Balkan States achieve better results than the post-soviet states; however, there are some common weaknesses: low quality of the education system and inefficient financial system, and rigid labour market in Albania, Croatia and Romania and underdeveloped political system in Bosnia and Herzegovina.
Keywords: diversity of capitalism; Balkan States; institutional complementarities; post-socialist countries; O11; O52; P16